Association between subject functional status, seat height, and movement strategy in sit-to-stand performance. - Mazzà C; Benvenuti F; Bimbi C; Stanhope SJ (Journal of the American Geriatrics Society, 2004)
OBJECTIVES: To explore the association between an individual's functional status, movement task difficulty, and effectiveness of compensatory movement strategies within a sit-to-stand (STS) paradigm. DESIGN: Cross-sectional study. SETTINGS: Rehabilitation unit of the Istituto Nazionale Riposo e Cura Anziani Geriatric Hospital of Florence, Italy. PARTICIPANTS: A convenience sample (131 subjects) of the outpatient clinic and day-hospital population. MEASUREMENTS: A performance-based test (repeated chair standing) was used to divide the subjects into five functional groups. Subjects performed a series of single STS tasks across a range of five descending seat heights. They were instructed to stand without using arms or compensatory strategies. If unable, swinging the arms was allowed, and if the inability persisted, subjects could push with their arms during subsequent attempts. The strategy or inability to stand formed the dependent measures. RESULTS: Subjects within the two highest functional groups could complete the single STS task at all seat heights, with a slight increased use of compensatory strategies at the lowest seat height. The effectiveness of the compensatory strategies decreased rapidly as a function of seat height and functional status. One-third (35.5%) of the subjects in the middle functional group swung their arms at the lower seat heights. Across the three least functional groups, 11.8%, 30.6%, and 83.3% of the subjects, respectively, were unable to stand at the lowest seat height. CONCLUSION: The individual's functional status and difficulty of the task influenced the effectiveness of a compensatory strategy to maintain the ability to stand, supporting the idea that disability depends on the interplay between environmental demands and physical ability.